Antiulcerogenic and analgesic effects of the Austroplenckia populnea extracts in mice - Seito, L. N.; Mazaro, R.; Di Stasi, L. C. (Wiley-Blackwell, 2002)
Austroplenckia populnea (Reiss.) Lund. is a Brazilian Cerrado plant belonging to the Celastraceae family. Hexane and methanol extracts of leaves were investigated for their antiulcerogenic (ethanol and indomethacin/bethanecol induced gastric damage) and analgesic (writhing and tail-flick tests) activities in mice. Acute toxic effects also were evaluated. Oral administration of both extracts at a dose of 1000 mg/kg significantly reduced the total area of the lesion, the relative area of lesion and the ulcerative index in ethanol-induced gastric damage, but both extracts were inactive in the indomethacin/bethanecol-induced gastric damage test. A dose dependent effect was determined with the hexane extract in the ethanol-induced lesions test. The hexane and methanol extracts reduced the number of contortions in the writhing test, but both extracts were inactive in the tail-flick immersion test. Copyright (C) 2002 John Wiley Sons, Ltd.
Keywords: medicinal plants; antiulcerogenic; analgesic; Celastraceae; Austroplenckia populnea